A relação onto-antropológica de cuidado de perigo como limite a expansão da política criminal em face da dogmática penal – uma abordagem sobre a presunção de inocência e a ADC 43/DF - Saraiva, Isaac Ronaltti Sarah da Costa (Universidade do Vale do Rio dos Sinos, 2020)
Through the analysis of Faria Costa's onto-anthropology, the objective is to know if the care-of-danger relationship would serve as a mechanism to limit a harmful interference of criminal policy in the face of criminal dogmatics in the act of deciding a process - propitious scenario breach of process guarantees and relativization of rights. In this research, the scenario of changes and interferences of foreign decision methods appropriate to Brazilian law is also analyzed, identifying in which measures issues such as legal realism contribute to an intense process that disregards criminal dogmatics, disregards a hierarchical logic of laws generating legal insecurity and contributing for phenomena like Judicial Activism. Choosing the concept of actuarial criminal policy will be worked out as judicial decisions start to use research and the empirical reality to support positions that differ from the function and purpose indicated by the criminal dogmatic framework. Methodologically supported by the Hermeneutic Criticism of Law, the question of the presumption of innocence is used based on the case of ADC 43 / DF as a study cell. Nowadays there is a constant attack on citizens' constitutional guarantees, in particular, the presumption of innocence, almost always making use of the argument that guarantees such as the presumption of innocence would be part of the cause of the Brazilian procedural slowness, as well as the presumption of innocence being responsible for the inefficiency of the Brazilian prison system - an argument nowadays worked on by an existing trend in the Supreme Court that is based on a discourse that the presumption of innocence, exercised in its fullness, would act as an obstacle to general prevention and proper functioning of the criminal justice system. Faria Costa defends an onto-anthropological proposal that diverges from a functional matrix and sees law and justice as a recomposition of an initial state of care for man towards his neighbor.
Keywords: Política criminal atuarial; Dogmática penal; Ativismo judicial; Realismo jurídico; Presunção de inocência; Onto-antropologia; Actuarial criminal policy; Penal dogmatics; Judicial activism; Legal realism; Presumption of innocence; Onto-anthropology; ACCNPQ::Ciências Sociais Aplicadas::Direito